Damping-off in Conifer Nurseries in India - Ram Reddy, M. A. (Indian Forester, 1969)
In India, plantations of indigenous species of conifers are raised on a large scale and also those of exotics on trial basis. The planting stock is raised in the nursery in which mortality soon after germination, popularly known as damping-off disease, is serious. Symptoms of damping-oft, causal organisms and the extent of damage in some nurseries are described. Control measures outlined include cultural practices in which the nursery soil should have light texture and acid pH (4.5) and through use of chemicas such as Thiram 75% W.P. (Tetramethyl thiram di-Sulphide) is recomened.